Psychophysiological predictors of mental adaptability among specialists of extreme profile (servicemen) - Kovaleva M.E.; Bulygina V. G. (Психология и право, 2017)
The results of a comprehensive psychological and psychophysiological study of the characteristics of mental self-regulation in the simulation of various stressful situations in the specialists of extreme profile on the example of servicemen were described in the article. The integrated protocol of the study by the method of biofeedback with consideration of various indices of the central and autonomic nervous system under conditions of stress stimulation was developed. The set of psychological questionnaires was used to diagnose psychological features of self-regulation: questionnaire of self-control H. Grasmik, questionnaire "Style of self-regulation of behavior" by V. I. Morosanova, the questionnaire BIS/BAS, the questionnaire formal - dynamic properties of individuality by V. M. Rusalov, personal questionnaire of the G. and S. Eysenck EPQ, the scale of anxiety Charles D. Spielberger. Statistical method of clustering by the k-means method, single-factor analysis of variance, multiple regression analysis were applied. Psychological and psychophysiological differences between mentally disadaptive and adaptive groups are described, as well as predictors of mental disadaptation for military personnel are identified. It was found that mental disadaptation among servicemen is characterized by a preference for simple tasks in the structure of self-control and a high level of reactive situational anxiety, reduced programming and evaluation indicators, psychomotor erbiness, intellectual speed, indices of psychomotor activity and general adaptivity. The psychophysiological profile of maladaptation differs from the normative indices with elevated indices of subcortical alpha and theta rhythms in the initial background, as well as an increased index of vegetative balance and a reduced index of activation of subcortical centers in the stress sample. Psychophysiological predicators of disadaptation were established.